SURFACE MATTERS THAN THE IMPLANT ITSELF-A REVIEW - Kannan, Sheela; Kurien, Anjana; EJMS, Editor (Eastern Journal of Medical Sciences, 2024)
Nowadays dental implants are a predictable and popular treatment option for tooth replacement in completely or partially edentulous patients. Implants are preferred over conventional treatment due to certain advantages it offers like preservation of bone; preservation of adjacent teeth, durability, better mastication and speech etc.Implant comes in direct bone contact and anchors through osseointegration. Successful osseointegration revolves around many factors such as biocompatibility of the implant material, quality and quantity of the available bone, surface treatment of the implant, loading and surgical protocol and various other systemic and local factors. Predictability of clinical success of dental implants can be enhanced by using newer materials or alterations in designs, surgical or loading protocols on the basis of available literature. Various studies have suggested that rough surface of implant enhances its integration with bone than a smooth implant surface. Several approaches are used to attain a rough surface and to improve the process of osseointegration of titanium dental implants. The present paper reviews different methods of treating implant surfaces to enhance bone implant interaction starting from the basic material used in dental implant manufacture.